The Tidal Model: analysis based on Meleis's perspective - Liane Araújo Teixeira; Ana Ruth Macedo Monteiro; Maria Vilani Cavalcante Guedes; Lúcia de Fátima da Silva; Maria Célia de Freitas
ABSTRACT Objective: To critically reflect on the conceptual components of the Tidal Model in the application of the mental healthcare process. Method: Critical analysis based on the Models of Theory Analysis, focused on the clarity and consistency of the theoretical components of the Tidal Model. Results: The clarity of the theory was verified through the demonstration of the following components: functional, presuppositions, concepts and propositions. The consistency is due to the possibility of proven application in several countries with different populations. Conclusion: There is a vast field of research and possibilities of application in the Brazilian nursing consultation, in search of usefulness and support in nursing care.